Microbiological surveillance of hospital environment in a Medical College Hospital in Kathmandu, Nepal - Pradhan, SB; Shrestha, CD (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Hospital acquired infections (HAI) are serious problems in the patient care and management despite antimicrobial therapy and advances in supportive care in developing countries. Regular cleaning following institutionalized guidelines of infection control policies can minimize the possibility of contamination and prevent the HAI so that the morbidity and mortality related to HAI will be reduced. MATERIALS AND METHODS: Descriptive analysis of the culture growth of the samples from different sites of the Kathmandu Medical College Teaching Hospital (KMCTH) environment from 4th March, 2011 to 4th April, 2012 was done. The swabs were taken before and after fumigation and disinfection and number of colonies grown were used to monitor the effectiveness of the intervention. The cultures and Gram staining were performed as per standard microbiological procedures in Clinical Microbiology Laboratory, Department of Pathology, Kathmandu Medical College Teaching Hospital. RESULTS: Almost all the floors of the hospital wards swabbed were contaminated with the bacteria. The bacteria that grew from the environment ranged from 50 to 140 colonies in Medical Intensive Care Unit and Special High Care Unit respectively. Common contaminants were Staphylococci spp., Gram negative diplococcic, and Gram positive. The Staphylococci spp. contaminated air in most of the wards. The number of colonies after fumigation and disinfection were drastically decreased from no growth to 15 colonies. CONCLUSIONS: Environment was contaminated with microorganisms. Even after regular cleaning and disinfection, bacterial growth was seen. To prevent any contamination prior HAI develops, hospital needs to develop programmes for the implementation of good infection control practices. DOI: http://dx.doi.org/10.3126/ijim.v1i2.7410 Int J Infect Microbiol 2012;1(1):76-79